Homoeopathic Management of Allergic Contact Dermatitis – A Case Report (Advancements in Homeopathic Research, 2025)
Allergic contact dermatitis is an inflammatory  skin condition caused by a type 4 hypersensitivity  reaction. It occurs when an irritant or allergen comes  into contact with the skin, triggering a T-cell mediated  response. The appearance and location of the  dermatitis often help identify the causative agent. For  example, dermatitis around the wrist might indicate  an allergic reaction to a bracelet or watchband.1 In this case report we present a case of allergic  contact dermatitis, presenting with complaints of  severe itching and burning on left dorsum of hand  with cracks and dryness of skin, bloody discharge  on scratching for 2 months, itching aggravated in  cold weather. After complete case taking and proper  repertorisation, on the basis of totality of symptoms  Petroleum 30 was prescribed.
Keywords: Homoeopathy; allergic contact dermatitis; Petroleum